KONTRIBUSI USAHA PABRIK PEMBUATAN RAK TELUR TERHADAP PENINGKATAN PENDAPATAN BAGI MASYARAKAT DI DESA CIPOTAKARI KABUPATEN SIDENRENG RAPPANG (STUDI KASUS PADA MBM EGG TRAY GROUP) - Irga Ayu Permadi; Sofyan B; Muhammad Rusdi; Pratiwi Ramlan (Journal of Innovation Research and Knowledge, 2025)
This research focuses on the contribution of the egg tray manufacturing business operated by Mitra Bina Mandiri (MBM) Egg Tray Group to increasing community income in Cipotakari Village, Sidenreng Rappang Regency. The study aims to analyze the business’s contribution to improving income levels and reducing the unemployment rate among the local population. A descriptive qualitative method was used, and data analysis was systematically conducted through the stages of data collection, reduction, coding, and presentation with the assistance of Nvivo 12 Plus software. The results show that the presence of Mitra Bina Mandiri (MBM) Egg Tray Group has had a positive impact by creating new job opportunities, especially for residents who previously did not have permanent employment. The structured work system and the use of recycled raw materials further strengthen the business’s contribution to increasing income and improving community welfare. This study also emphasizes that micro-enterprises based on local potential can serve as a concrete solution for sustainable rural economic development and community empowerment.